Milton's Paradise lost - Ryken, Leland (Wheaton, Ill. : Crossway, 2013)
Guides readers through the paramount epic in the English language, Milton's Paradise Lost, and showcases Milton's understanding of crime and punishment in the events of creation, the fall, and redemption. Part of the Christian Guides to the Classics series.
The Nature and Function of Literature -- Why the Classics Matter -- How to Read a Story -- Paradise Lost: The Book at a Glance -- The Author and His Faith -- Paradise Lost as Epic and Anti-Epic -- Preliminary Considerations -- Paradise Lost -- Leading Topics in Paradise Lost: The Big Ideas in the Poem.
Includes bibliographical references (page 91).
Keywords: Milton, John, -- 1608-1674.; Christianity and literature